Interaction of Palm Fatty Acid Distillate (PFAD) and High-Tannin Mangrove Fruit Extract (Sonneratia alba) on the In Vitro Digestibility of Fiber Fractions in Dairy Cattle Feed - Elihasridas; Roni Pazla; Antonius; Gusri Yanti; Zaitul Ikhlas; Yelly Fitri; Jenni Zulfadillah; Meiko Armanda Bariva; Muhammad Arief Subhi; Natasya Triana; Todif Elfindo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aimed to evaluate the interaction between Palm Fatty Acid Distillate (PFAD) and high-tannin mangrove fruit extract (Sonneratia alba) on the in vitro digestibility of dairy cattle feed fiber fractions. The experimental design used a completely randomized factorial 3×4 pattern with three replicates. The first factor was the PFAD level (0%, 3%, 6%) and the second factor was the mangrove fruit extract dose (0%, 0.5%, 1%, 2%). Fermentation was carried out using the Tilley and Terry (1963) rumen stage method using fresh goat rumen fluid. The parameters observed included the digestibility of neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, and cellulose. The results showed that PFAD, mangrove fruit extract, and their interaction had a significant effect (P<0.05) on the digestibility of NDF and cellulose, but did not have a significant effect on ADF and hemicellulose. The combination of 3% PFAD and 0.5–1% extract provided the highest digestibility. Increasing PFAD and tannin reduced digestibility due to the fat coating effect and the formation of tannin complexes with structural carbohydrates. The combination of PFAD and mangrove tannin can be optimized as a functional feed additive based on local resources that improves rumen fermentation efficiency without reducing fiber digestibility.